Associations between composite dietary antioxidant index and estimated 10-year atherosclerotic cardiovascular disease risk among U.S. adults - Zhang, Jia; Lu, Xueqin; Wu, Ruifeng; Ni, Hanchen; Xu, Lingli; Wu, Wenjuan; Lu, Cheng; Feng, Jiayi; Jin, Yongmei (Frontiers in Nutrition, 2023)
Background: Atherosclerotic cardiovascular disease (ASCVD) remains the leading cause of death and disability both in U.S. and worldwide. Antioxidants have been proved critical in mitigating the development of atherosclerosis. This study aimed to investigate the associations between composite dietary antioxidant index (CDAI) and estimated 10-year ASCVD risk among U.S. adults. Methods: Data extracted from the National Health and Nutrition Examination Survey were analyzed. A total of 10,984 adults aged 18 years and above were included in this study. CDAI was calculated based on the dietary intake reported in their 24-hour recall interviews. The estimated 10-year ASCVD risk was calculated via Pooled Cohort Equations (PCE). Results: After adjusting potential confounders, it was indicated that CDAI score was negatively correlated with 10-year ASCVD risk (OR 0.97, 95% CI 0.95-0.99). Stratify CDAI score by quartile, results showed that participants in the second, third, and fourth quartiles had lower ASCVD odds ratio (Q2: OR 0.87, 95% CI 0.69-1.09; Q3: OR 0.78, 95% CI 0.62-0.98; Q4: OR 0.74, 95% CI 0.59-0.94) than those in the first quartile (Q1, lowest CDAI score group), which was confirmed by the trend test as well (P < 0.05). Subgroup analyses stratified by sex, age, race/ethnicity, and smoking status did not show significant effect modification. Conclusion: Higher dietary antioxidants intake is associated with lower ASCVD risk among U.S. adults, for which policymakers and healthcare professionals may consider increasing the consumption of antioxidant-rich foods as a preventive strategy for ASCVD.